Lorentz and CPT violation - Potting, Robertus (2018)
During the past two decades there has been a growing interest in the possibility that Lorentz and/or CPT might not be exact symmetries of Nature. In this short review, we present the current state of affairs, addressing both theoretical and experimental/observational issues. We pay particular attention to the role that has been played by the so-called Standard Model Extension